2006
DOI: 10.1098/rspa.2006.1729
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of large ocean waves: the role of local and rapid spectral changes

Abstract: This paper concerns the formation of large-focused or near-focused waves in both unidirectional and directional sea-states. When the crests of wave components of varying frequency superimpose at one point in space and time, a large, transient, focused wave can occur. These events are believed to be representative of the largest waves arising in a random sea and, as such, are of importance to the design of marine structures. The details of how such waves form also offer an explanation for the formation of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 31 publications
(51 reference statements)
7
70
1
Order By: Relevance
“…In this latter case the energy transfers occur in a random sea and are characterized as being extremely slow, a small percentage of the total energy being transferred over hundreds of wave cycles. In contrast, Johannessen & Swan (2003) and Gibson & Swan (2007) showed that, in a deep-water-focused wave group, with the phasing far from random but the surface profile believed to be representative of an extreme wave event, the local nonlinearity is such that the third-order resonant interactions can be responsible for highly localized and very rapid energy transfers. In this case, significant energy transfers can occur over 5-10 wave cycles immediately preceding the extreme wave event.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this latter case the energy transfers occur in a random sea and are characterized as being extremely slow, a small percentage of the total energy being transferred over hundreds of wave cycles. In contrast, Johannessen & Swan (2003) and Gibson & Swan (2007) showed that, in a deep-water-focused wave group, with the phasing far from random but the surface profile believed to be representative of an extreme wave event, the local nonlinearity is such that the third-order resonant interactions can be responsible for highly localized and very rapid energy transfers. In this case, significant energy transfers can occur over 5-10 wave cycles immediately preceding the extreme wave event.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, Gibson & Swan (2007) applied the ZE model to describe the evolution of a number of deep-water wave cases. In outlining the theory they also demonstrated the validity of comparisons between the BST and ZE models.…”
Section: (B) Wave Model 2: Zementioning
confidence: 99%
See 1 more Smart Citation
“…Linear waves when superposed add together linearly, so that their combined amplitude is the sum of the amplitudes of the components, but for nonlinear waves this is no longer true, and when two solitons coincide the combined height may be far greater than the sum; this has been postulated as a possible mechanism for the occurrence of freak waves. [44][45][46] In Hokusai's image we see the trailing slope of another large wave at the right of the picture, as if perhaps there is a group of freak waves, and at the left behind the great wave we glimpse a smaller wave that might be one of those colliding to produce the freak wave. Although he produced the image long before there existed any scientific understanding of freak waves, and Hokusai may well have exaggerated the wave height for artistic effect, it is possible that he could have painted The great wave off Kanagawa after hearing sailors tell of such a monster.…”
mentioning
confidence: 99%
“…Realistic fully nonlinear computations wave by wave over large areas are very challenging, but initial attempts have been made to simulate the ocean surface using the full Euler equation both on large scales [Tanaka, 2001] and over smaller areas [Gibbs and Taylor, 2005;Gibson and Swan, 2007]. However, in this paper, we rely on series expansions, resulting in a sequence of approximations.…”
Section: Introductionmentioning
confidence: 99%